2010
DOI: 10.1037/a0018482
|View full text |Cite
|
Sign up to set email alerts
|

The hidden consequences of racial salience in videotaped interrogations and confessions.

Abstract: Evaluations of videotaped criminal confessions can be influenced by the camera perspective taken during recording. Interrogations and confessions recorded with the camera directing observers' visual attention onto the suspect lead to biased judgments of the suspect. Although a camera perspective that directs visual attention onto the suspect and interrogator equally appears to promote unbiased judgments, investigations to date have relied on videotapes that depict only Caucasian suspects and interrogators. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 64 publications
3
30
0
Order By: Relevance
“…Indeed, activating the social category Black has been demonstrated to have negative consequences on legal judgments [12] . The effect of attention and perceptions of guilt is especially salient for minority groups [26] , so priming attention to minority racial groups in a judicial setting is particularly troublesome. Similarly, because Black has been shown to be implicitly associated with Guilty, compared to White and Not Guilty, it would be surprising if this finding were completely reversed in the current research paradigm.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, activating the social category Black has been demonstrated to have negative consequences on legal judgments [12] . The effect of attention and perceptions of guilt is especially salient for minority groups [26] , so priming attention to minority racial groups in a judicial setting is particularly troublesome. Similarly, because Black has been shown to be implicitly associated with Guilty, compared to White and Not Guilty, it would be surprising if this finding were completely reversed in the current research paradigm.…”
Section: Discussionmentioning
confidence: 99%
“…Such stereotypes may directly increase the perceived truth of a suspect's confession, as several studies have shown. For instance, Ratcliff and Lassiter ( 2010 ) showed participants scripted videotaped interrogations of Black, Chinese, or White suspects conducted by a White interrogator. The defendant confessed to a hit-and-run offense.…”
Section: Judging the Confession: Is It Voluntary And True?mentioning
confidence: 99%
“…Participants then watched the interrogation video. The interrogation video was obtained from G. Daniel Lassiter, and a similar version has been used in previous research (e.g., Ratcliff et al, 2010). The video was derived from a transcript used in prior research (Kassin & McNall, 1991), and filmed from an equal-focus camera perspective (i.e., both the interrogator and suspect profiles were visible).…”
Section: Trial Summarymentioning
confidence: 99%